THE ROLE OF THE VILLAGE GOVERNMENT IN SUPPORTING CORN FARMING COMMUNITY INCOME - Wokanubun, Paulina (Uniqbu Journal of Social Sciences, 2022)
Study this conducted in office Village La la Subdistrict Namlea. Role Government Village in empowerment Public in Village La la Subdistrict Namlea, Buru Regency, really important to support conditions this village because most of the people in this village have a livelihood as farmers corn so that it is possible in the empowerment of corn plants. Destination The purpose of this study is to determine and analyze the role of the village government and what factors which encourage and hinder the role of village government in support income Public farmer corn in Village La la Subdistrict Namlea, Buru Regency. The results showed that the village government La la hold role important for determine step which appropriate in increase the income of corn farmers or empower the community in Lala Desa Village Namlea District.